Arginine methylation of METTL14 promotes RNA N 6-methyladenosine modification and endoderm differentiation of mouse embryonic stem cells - Xiaona Liu (Nature Portfolio, 2021)
The methyltransferase complex of METTL3-METTL14-WTAP is responsible for m6A modification on RNA. Here the authors report that METTL14 arginine 255 (R255) is methylated by PRMT1 and this modification increases interaction of METTL3/METTL14 interaction with WTAP and substrate RNA, promoting m6A methylation activity of the complex.